Manajemen Komunikasi Organisasi Kantor Pelayanan Pajak Pratama Bengkalis Dalam Kegiatan Penerimaan Surat Pemberitahuan Tahunan Pajak Penghasilan - Megawati; Suwardi Lubis; Lusiana Andriani Lubis (PERSPEKTIF, 2023)
The purpose of this study was to analyze organizational communication management, communication barriers, and efforts to overcome communication barriers faced by tax officials and taxpayers in the implementation of activities for receiving Annual Tax Returns (SPT) Income Tax (PPh) at the Pratama Bengkalis Tax Office (KPP). The theory used: the theory of communication management and organizational communication. This study uses a constructivist paradigm with a qualitative approach. The research subjects totaled 107 employees and the determination of informants was carried out using a purposive technique, so that 7 (seven) informants were obtained. The results of the study show that organizational communication management includes 4 stages: planning, by setting activity targets; organizing, namely dividing the work; actuating, namely providing direction and motivating; and controlling by observing the implementation of activities in the field, providing solutions, and evaluating. Communication barriers include internal barriers in the form of horizontal communication between employees. External barriers, namely public communication to organizations, such as remote locations for taxpayers to consult and network disruptions; and organizational communication to audiences, such as decoding, communicative, technical, language differences, perception, and psychosocial barriers. Efforts to overcome this by optimizing services through face-to-face and media socialization, providing additional service posts, building intensive personal communication between employees, creating a sense of empathy between tax officials and taxpayers, and optimizing the role of opinion leaders.